Correlation between Uric Acid Levels and the Severity of Psoriasis Vulgaris Patients - Pristia Widya Monica; Nurrachmat Mulianto (Indonesian Rheumatology Association, 2023)
Introduction: Psoriasis vulgaris (PV) is a recurrent chronic inflammatory skin disease characterized by erythematous, scaly, well-defined plaques with the greatest predilection, generally in the areas of the elbows, knees, scalp, and lower back. The psoriasis area and severity index (PASI) is one of the most widely used evaluation tools to determine the development of psoriasis vulgaris in a patient. Hyperuricemia is the dominant risk factor for PV when compared to other known risk factors, such as obesity or metabolic syndrome. This study aimed to determine whether there is a relationship between serum uric acid levels and the severity of PV based on the PASI score. Methods: Cross-sectional study with one-time sampling conducted from December 2021 to February 2022 in psoriasis vulgaris patients who came to the Dermatology and Venereology clinic at Dr. Moewardi General Hospital, Surakarta, Indonesia. All data were statistically analyzed using SPSS 26. Variables, including age, gender, disease duration, body mass index, and uric acid levels, were subjected to univariate analysis. Bivariate analysis was then followed by a parametric test. The p-value <0.05 was considered significant. Results: There were 36 patients during the study period. The average uric acid level was 6.0135, with an average PASI score of 10.6388. The relationship between uric acid levels and the severity of psoriasis vulgaris was found to be significant, with a value of p = 0.025. Conclusion: There is a significant relationship between uric acid levels and the severity of psoriasis vulgaris, where the higher the uric acid level, the more severe the severity of psoriasis vulgaris.